2023
DOI: 10.3389/fneur.2023.1292372
|View full text |Cite
|
Sign up to set email alerts
|

Association between bronchopulmonary dysplasia and death or neurodevelopmental impairment at 3 years in preterm infants without severe brain injury

Wenli Li,
Yong Wang,
Juan Song
et al.

Abstract: ObjectiveWe investigated the association between bronchopulmonary dysplasia (BPD) and 3 years death or neurodevelopmental impairment (NDI) in very preterm infants without severe brain injury.MethodOur prospective cohort study recruited preterm infants who were born prior to 32 weeks of gestational age and survived in the neonatal intensive care unit until 36 weeks of corrected age. Upon reaching 3 years of age, each infant was assessed for death or NDI such as cerebral palsy, cognitive deficit, hearing loss, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Bronchopulmonary dysplasia (BPD) is the most common serious complication of very preterm infants (VPI) or very low birth weight (VLBW) infants, affecting up to 45% of infants born at less than 29 weeks gestational age (GA) [1]. There is a strong correlation between the severity of BPD and mortality, poor respiratory prognosis, persistent pulmonary hypertension, and neurodevelopmental impairment (NDI) in preterm infants [2][3][4][5]. A Canadian investigation found that BPD and its associated complications result in an extreme cost burden early in life and a lifelong negative impact on quality of life for preterm infants with a GA ≤ 28 weeks [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bronchopulmonary dysplasia (BPD) is the most common serious complication of very preterm infants (VPI) or very low birth weight (VLBW) infants, affecting up to 45% of infants born at less than 29 weeks gestational age (GA) [1]. There is a strong correlation between the severity of BPD and mortality, poor respiratory prognosis, persistent pulmonary hypertension, and neurodevelopmental impairment (NDI) in preterm infants [2][3][4][5]. A Canadian investigation found that BPD and its associated complications result in an extreme cost burden early in life and a lifelong negative impact on quality of life for preterm infants with a GA ≤ 28 weeks [6].…”
Section: Introductionmentioning
confidence: 99%